NSGA-II APPLICATION METHOD ON MULTI-OBJECTIVE PROFIT-LOSS SHARING OPTIMIZATION PROBLEM IN SHARIA INVESTMENT - Mustika, Tika
The traders in traditional markets requires substantial capital to develop their business in order to survive in competition with the modern market. Conventional bank provide the capital, but they still use the conventional system of interest rate which is forbidden by our religion. Thus we need to be applied a provit-loss sharing scheme of the investment which are accordance with the Islamic Sharia system that use prot sharing ratio as their provit instrument. In determining prot-sharing ratio, the calculation should be done precisely in order to provide the benet to the owners of capital and the fund manager. So the optimization problem is to maximize prots of investors and maximize the portion of the trader. In this thesis, optimization of prot-loss sharing ratio for a large variety and periods of loan are solved using Elitist Non-Dominated Sorting Genetic Algorithm (NSGA-II) which is one of the methods multi-objective evolutionary algorithm (MOEA).